2011
DOI: 10.1159/000330750
|View full text |Cite
|
Sign up to set email alerts
|

A Blood-Based Algorithm for the Detection of Alzheimer’s Disease

Abstract: Background: We previously created a serum-based algorithm that yielded excellent diagnostic accuracy in Alzheimer’s disease. The current project was designed to refine that algorithm by reducing the number of serum proteins and by including clinical labs. The link between the biomarker risk score and neuropsychological performance was also examined. Methods: Serum-protein multiplex biomarker data from 197 patients diagnosed with Alzheimer’s disease and 203 cognitively normal controls from the Texas Alzheimer’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 63 publications
1
75
1
Order By: Relevance
“…The major lesions associated with AD are amyloid plaques and neurofibrillary tangle formation. Previous studies have also indicated some candidate screening biomarkers for AD such as tau and phosphorylated tau in saliva [8], and α-2-macroglobulin, amyloid, and apolipoproteins in serum [9][10][11]. The most reproducible findings were decreased expression of β-amyloid 1-42 and increased expression of tau and phospho-tau (ptau-181) in CSF samples [6,8,[12][13][14].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The major lesions associated with AD are amyloid plaques and neurofibrillary tangle formation. Previous studies have also indicated some candidate screening biomarkers for AD such as tau and phosphorylated tau in saliva [8], and α-2-macroglobulin, amyloid, and apolipoproteins in serum [9][10][11]. The most reproducible findings were decreased expression of β-amyloid 1-42 and increased expression of tau and phospho-tau (ptau-181) in CSF samples [6,8,[12][13][14].…”
mentioning
confidence: 97%
“…It is important to develop a reliable and accurate clinical blood test method for AD. In previous studies, blood-or serum-based biomarkers for the detection of AD were reported [7][8][9][10][11]14,16]. Blood-based biomarkers are possible and plausible, but more work has to be done to carefully examine the design of studies, the collection and accessibility of cohorts and samples, and the use of technologies [7].…”
mentioning
confidence: 99%
“…In the current study, 5 of the top 10 AD markers (I309, IL-5, TN-C, IL-7 and CRP) overlapped with the top 10 markers from our recently cross-validated 21 serum-based biomarker panel [18]. An additional 4 biomarkers of the top 10 AD markers (THPO, eotaxin 3, TN-C, and IL-7) overlapped with the top 10 markers among 30 markers associated with AD among non-Hispanic whites [16]. In contrast, Panamanians and US Mexican Americans have one marker (B2M) in common among the top 10 markers of AD.…”
Section: Discussionmentioning
confidence: 72%
“…Evidence shows that brain imaging and cerebrospinal fluid biomarkers are highly accurate in detecting disease presence; however, these methods are not cost-and time-effective strategies for primary care clinical settings particularly in low-resource settings. In this regard, recent research into blood-based biomarkers of AD has produced encouraging results that suggest that blood-based screening is a viable approach to early diagnosis [13][14][15][16][17][18][19][20]. Together, the results of these studies provide strong evidence that a blood-based screening approach can be useful in discriminating AD from healthy controls as well as from other dementias [21].…”
mentioning
confidence: 95%
“…This protein does not have sulph-hydryl group to scavenge heavy metals like mercury. Over-production of Ab may associate arsenic induced inflammatory response and oxidative stress in brain [177,178]. Lead is most potent Ab inducer, followed by cadmium and minor arsenic effect.…”
Section: Studies On Disruptive Exposurementioning
confidence: 99%